2019
DOI: 10.1007/s00248-019-01391-x
|View full text |Cite
|
Sign up to set email alerts
|

Alphacoronavirus Detection in Lungs, Liver, and Intestines of Bats from Brazil

Abstract: Bats are flying mammals distributed worldwide known to host several types of Coronavirus (CoV). Since they were reported as the probable source of spillover of highly pathogenic CoV into the human population, investigating the circulation of this virus in bats around the world became of great importance. We analyzed samples from 103 bats from two distinct regions in Brazil. Coronavirus from the Alphacoronavirus genus was detected in 12 animals, 11 from São José do Rio Preto-SP region and 1 from Barreiras-BA re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 62 publications
3
23
2
Order By: Relevance
“…However, in each study of natural infection the prevalence ranged between 0.9% [ 31 ] and 33.3% [ 45 ]. Coronavirus prevalence rates in bats have been reported to typically range from 3% to 10% [ 30 ], and a global study with more than 12,000 samples reported a rate of 8.6% [ 15 ]. Such estimates may be influenced by factors such as the geographic regions involved, the number of species analyzed in each study, the heterogeneity of the collection sites, the type of samples analyzed, and the number of individuals sampled [ 15 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, in each study of natural infection the prevalence ranged between 0.9% [ 31 ] and 33.3% [ 45 ]. Coronavirus prevalence rates in bats have been reported to typically range from 3% to 10% [ 30 ], and a global study with more than 12,000 samples reported a rate of 8.6% [ 15 ]. Such estimates may be influenced by factors such as the geographic regions involved, the number of species analyzed in each study, the heterogeneity of the collection sites, the type of samples analyzed, and the number of individuals sampled [ 15 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Coronavirus prevalence rates in bats have been reported to typically range from 3% to 10% [ 30 ], and a global study with more than 12,000 samples reported a rate of 8.6% [ 15 ]. Such estimates may be influenced by factors such as the geographic regions involved, the number of species analyzed in each study, the heterogeneity of the collection sites, the type of samples analyzed, and the number of individuals sampled [ 15 , 30 ]. This review found that only three of the 25 studies examined samples from more than one country, and studies that examined a greater number of species also recorded a greater number of species positive for coronavirus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1A). All four vampire bat sequences are novel α-CoVs and displayed the most genetic similarity (94.6−97.3 %) to human CoVs (HCoVs; HCoV-NL63 and HCoV-229E) rather than known bat α-CoVs, including those previously found in other vampire bat colonies and other Neotropical bat species more broadly (Asano et al, 2016; Bittar et al, 2020). Univariate logistic regressions did not find significant (unadjusted) effects of any bat demographics on CoV positivity.…”
Section: Resultsmentioning
confidence: 80%